The Impact of Service Quality and Trust in Early Childhood Education: Why Parents Stay—or Walk Away? - Fadilah, Fadilah; Ningsih, Arie Dwi; Hasibuan, Rabitah Hanum (Seulanga : Jurnal Pendidikan Anak, 2025)
Improving service quality is one of the marketing strategies that emphasizes the fulfillment of customer desires. Good service quality will increase customer satisfaction. Thus, parents will trust the school if they are satisfied with the quality of its services. The more parents trust the school, the higher their satisfaction level will be. This study aims to identify the factors influencing parent satisfaction at RA Nurul Hikmah Binjai Timur. Service quality and trust are hypothesized to influence parent satisfaction. This study employs a quantitative method. Data collection techniques include questionnaires and interviews. The sampling method in this study uses random sampling with the Slovin formula at a 5% level, resulting in a sample size of 45 respondents. Data analysis in this study uses multiple linear regression analysis with the assistance of SPSS 25 software. The results of this study indicate that service quality and trust have a positive and significant influence on the satisfaction of parents of students at RA Nurul Hikmah Binjai Timur.